A Technical Report on Rate Analysis and Dressing Feed Rate of Courts Megastore’s Information Technology Processes (Global Journal of Management and Business Research, 2025)
The proposal discusses about the information technology and information systems infrastructure underpinning the organisation for this project Courts Megastore Singapore Courts Singapore is a retail outlet that is a one-stop retail and furnishing solution that offers different household and electronic products in various locations in Singapore It is a listed company that is owned by the Courts Group International Limited Singapore It has released according to its press announcements approximately 57 09 of the shares to Singapore Retail Group Ltd as the main owner The new format of Courts resulted in a Big Box Courts Megastore solution which is unlike the previously silos-formatted retail shops The said megastore was opened on 16 December 2006 and focused on key elements such as the combination of a traditional focus on value with a more experiential and service-orientated layout In 2007 the group sales increased by 8 1 from S 308 3 m to S 333 4 m from 2006 due to having placed vital products at the forefront of the retail stores as well as the gradual cessation of many non-performing retail outlets in other parts of Singapore Courts Singapore Limited 2008
Keywords: courts; retail; information technology; information system; network operating system; microsoft management console; remote access services